2019
DOI: 10.1038/s41390-019-0391-y
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal changes in the gut microbiome of infants on total parenteral nutrition

Abstract: Background: Animal studies suggest that total parenteral nutrition (TPN) may alter bacterial colonization of the intestinal tract and contribute to complications. Progressive changes in gut microbiome of infants receiving TPN are not well understood. Methods: Infants with and without TPN/soy lipid were enrolled in a prospective, longitudinal study. Weekly fecal samples were obtained for the first 4 weeks of life. High throughput pyrosequencing of 16S rDNA was used for c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 40 publications
1
30
0
1
Order By: Relevance
“…Although post-HSCT enteral feeding is being increasingly recommended [37][38][39], intravenous nutrient intake (PN) is still the first-line nutritional approach for the patients who received HSCT due to its compliance, but it has been associated with several clinical and microbiological adverse effects, including infections and GM dysbiosis [18][19][20][21][22][23][24]. So far, the central role of the GM composition and biodiversity in patients undergoing HSCT has been largely evaluated in several publications, highlighting the disruption of the gut microbial mutualistic asset after the transplant (i.e., until 30 days post-HSCT) compared to the baseline, due to all HSCT conventional treatments that can alter the GM recovery possibilities post-HSCT [4,5,7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although post-HSCT enteral feeding is being increasingly recommended [37][38][39], intravenous nutrient intake (PN) is still the first-line nutritional approach for the patients who received HSCT due to its compliance, but it has been associated with several clinical and microbiological adverse effects, including infections and GM dysbiosis [18][19][20][21][22][23][24]. So far, the central role of the GM composition and biodiversity in patients undergoing HSCT has been largely evaluated in several publications, highlighting the disruption of the gut microbial mutualistic asset after the transplant (i.e., until 30 days post-HSCT) compared to the baseline, due to all HSCT conventional treatments that can alter the GM recovery possibilities post-HSCT [4,5,7].…”
Section: Discussionmentioning
confidence: 99%
“…EN, also called "tube-feeding", is the method by which food is directly delivered inside the patient's gastrointestinal tract, while PN is an effective strategy of delivering nutrients directly into the bloodstream. Nowadays, it is well known that total PN, the first-line approach for HSCT patients, is associated with different clinical adverse effects such as infections [18][19][20] and metabolic disorders [21], as well as with gut mucosal atrophy [22], cell dysfunction [23], and alterations in GM composition [24]. Conversely, EN has been indicated as a possible solution to overcome all these adverse effects.…”
Section: Introductionmentioning
confidence: 99%
“…The colonization of pathogenic microbes, which leads to dysbiosis in preterm infants, is linked to the delayed introduction of human milk, early antibiotic intervention, a high rate of caesarean delivery, and total parenteral nutrition [152]. This last factor is associated with a lower abundance of Bacteroides and Bifidobacterium and a significant loss of biodiversity [153].…”
Section: The Use Of Probiotics and Paraprobiotics In Preterm Neonatesmentioning
confidence: 99%
“…Data regarding the changes in the microbiome of humans receiving parenteral nutrition are limited. However, studies performed in newborns receiving parenteral nutrition have reported progressive changes in their microbiome with a significantly lower abundance of Bacteroidetes and a greater abundance of Verrucomicrobia in comparison with the controls [81]. In addition, the enrichment of Clostridium species was observed [82,83].…”
Section: Enteral Versus Parenteral Nutrition: Effect On Gut Microbiomementioning
confidence: 99%